The Indonesian Commercial Banks' Profitability and Credit Risk - Setiawan, Ilham; Zulbetti, Rita; Perwito, Perwito (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study examines the impact of credit risk on the profitability of commercial banks listed on the Indonesia Stock Exchange (IDX) during the period 2013-2022. Using purposive sampling, 40 banks were selected from 47 listed banks. Panel data regression analysis was employed to explore the impact of credit risk, measured by Non-Performing Loans (NPL) and Loan Loss Provisions (LLP), on profitability measured by Return on Assets (ROA). The results indicate that NPL has a negative but insignificant effect on ROA, suggesting that an increase in NPL does not directly impact a decrease in ROA. Conversely, LLP has a negative and significant effect on ROA, indicating that an increase in LLP can reduce ROA as banks allocate substantial funds for loan losses, thereby affecting their profitability. Therefore, banks and regulators need to enhance credit risk management. This not only impacts banking profitability but also can maintain the overall stability of the financial system. Keywords: Credit Risk, Non-Performing Loan, Loan Loss Provision, Return on Assets, Bank Profitability.